Students’ Creative Thinking in Solving Open-Ended Problems in Geometry Transformation Material - Stefani Putri Andrianti; Subanji Subanji; Desi Rahmadani (Universitas Suryakancana, 2026)
This study aims to describe students’ creative thinking abilities in solving open-ended problems in geometry transformation material. The problem used in this study was designed as a multiple solution task (MST) because it provides students with opportunities to generate more than one strategy or solution. This study employed a descriptive qualitative approach involving 27 students of Class XII-B at a Catholic senior high school in Surabaya. Data were collected through a written test and interviews and were then analyzed based on the indicators of fluency, flexibility, and novelty. The findings show that students were classified into three creativity groups. S1 represented the high-creativity group and demonstrated novelty through a non-routine strategy and by rechecking the solution. S2 represented the moderate-creativity group and demonstrated fluency and flexibility by producing more than one form of solution and using several methods, although the variation remained limited. S3 represented the low-creativity group and did not yet demonstrate fluency or flexibility because the student used only one method and produced a single answer. These findings indicate that open-ended problems in the form of MST can reveal differences in students’ creative thinking abilities in geometry transformation material. Keywords: creative thinking; open-ended; transformation geometry